Restorative Justice And Law Protection For Parents And Children : Case Of Human Trafficking In Indonesia - Suciyani Suciyani (BUANA GENDER : Jurnal Studi Gender dan Anak, 2020)
This research aims to analyse criminal law supremacy in a case of fighting against human trafficking. The problem of criminal law that relates to child trafficking is extremely serious and never-ending in this country. This case becomes an evaluation to reconsider the criminal law enforcement in Indonesia. Several legal solutions are executed by criminal law enforcement within the collaboration with the social communities and other countries to handle the problem of child trafficking. The concept of restorative justice and civil law protection is needed to be implemented by involving all parties, including parents as a family member. This study uses legal research as an approach and to gather the data; a legal settlement in handling child trafficking involves children and parents. Throughout this study, normative and empirical juridical approaches are used. It can be a great compatible recommendation and solution for handling the increase of child trafficking. On the other hand, from this study, it can be seen that the performance level of the individual that concerns on law enforcement process in Indonesia has implemented the paradigm of restorative justice in criminal law enforcement based from data that show an increase of child trafficking. Indicators of criminal law enforcement as a baseline to solve the child trafficking problem are about the level quality of legal protection of children. The role of family, law enforcement, government, NGO and social community leaders is very crucial to maintain the effectiveness of restorative justice and law protection of children involved in human trafficking in Indonesia. The involvement of parents by selling their children or getting their children as an entity in case of debt transaction causes the weakness of restorative justice and law protection of children in the problem of child trafficking. The significant results from this research are that criminal law enforcement against child trafficking that involves parents can improve the legal protection for future criminal law enforcement in Indonesia.